A model for Malaysian work value to improve level of work value among Malaysian graduate - Mohamad, Bahtiar; Zulkepli Hew, Jafri; Ismail, Ahmed Rageh; Abu Bakar, Hassan (Hampstead Psychological Associates, 2020)
Work values are the beliefs and ideas that are related to one’s occupation. These values are eventually used as guiding principles in career choice. Previous research examined work values and its impact or some relevant constructs such as affective commitment, organizational identification and self-efficacy. However, those relationships haven’t been collectively integrated and empirically tested in a theoretical model, nor have they been empirically tested. Therefore, this study aims to assess the influence of Malaysian Work Value Model (MWVM) on cooperative communication, affective commitment, organizational identification and self-efficacy. Latent composite structural equation modeling was used to test the hypothesized model. Finally, recommendations will be provided for the public and private universities to help them in developing their course learning outcome in order to enhance student’s work values and increase the employability rate.